Alzheimer’s dementia causing genes identification by meta heuristic approach - OIESWARYA BHOWMIK; M. MURALI (International Journal of Pharma and Bio Sciences, 2017)
With the advancement in the field of healthcare average life span of humans has increased; and thus there has been a substantial surge in the number of people being affected by the dementia disease. Alzheimer’s disease is considered as one of the most common form of dementia. It is a common term for memory loss and other abilities that cause serious damage in leading normal lives. Through years of research scientists have concluded that this disease, usually seen in older people, is a genetic disorder. Identifying the genes responsible for the disease has been carried out by several bioinformatics methods. In this study, a dataset of 33297 genes of 79 patients was studied to identify the genes that are critical for the disease and the study was conducted based on microarray gene expression. A small subset of genes has to be carefully chosen which can be identified for causing the disease. Selecting this small subset of disease critical genes encompasses a large search space hence, meta-heuristic algorithm Variable Neighborhood Search (VNS) has been applied. Fitness of the set of genes selected to be critical for the disease is determined by K Nearest Neighbor (kNN) method.